Factors affecting growth and toxin production of microcystis aeruginosa towards better water quality management in the Philippines and Cambodia - HUL Seingheng (2010.)
Cyanobacteria can survive abd grow in various types of aquatic habitat ranging from freshwater, brackish, and sea water. Cyanobacteria bloom is becoming an annoying problem in most countries in the world. Toxigenic Microcystis aeruginosa is a common blooming species of cyanobacteria in most water bodies. Knowing the factors and conditions for their growth, survival and bloom is important in the management and control of water bodies that are prone to their bloom and toxin contamination. For its management, water quality was monitored for a year in Tonle Sap lake of Cambodia. Turbidity, nitrate and phosphate levels in the lake were higher during the summer period April to May 2009. In May 2009, microcystins were found in Kompong Luong site and in an offshore site but the gene of toxic microcystis was found only in Kompong Luong site.
This study also aimed to determine the effects of some of the most relevant factors affecting the growth and toxin production of Microcystis aeruginosa: nitrate-N and phosphate-P levels and rario, light intensity, presence and dominance of non-toxic strain of the same species and presence of a potential predator or competitor bacteria. The results of the laboratory culture experiments showed that M. aeruginosa thrives well at high light intensity of 2,500 lux as compared to 900 lux, both at initial nitrate and phosphate levels of 57 and 1.4 ppm, respectively. At different levels of nitrate-N (0.1, 7 and 14ppm) and phosphate-P (0.1, 1 and 2 ppm), nitrate have a stronger influence on cell density and toxin levels. Cell density was negligible at 0.1 ppm nitrate than those at 7 and 14 ppm nitrate-N, regardless of the phosphate level. It was found that in the presence of non-toxic strain of the same species, M.aeruginosa produced more toxins than without the non-toxic strain. The extracellular toxin increased as the ration of the non-toxic to the toxic strain was increased.
The effect of the presence of potential predator bacteria isolated from compost was also determined. It was found that in the presence of the isolate, the growth and toxin production of the toxic M. aeruginosa significantly decreased. The use of the isolate showed a promising technique in controlling M. aeruginosa. However, further laboratory ecosystem research is still needed because this present work has not shown yet the effect of the presence of other organisms in aquatic environments.
Thesis (Ph.D. Environmental Engineering)--University of the Philippines, Diliman
Keywords: Cyanobacterial blooms; Microcystis aeruginosa; Water quality management -- Cambodia; Water quality management -- Philippines